The Emergence and Revival of Charismatic Movements: Argentine Peronism and Venezuelan Chavismo, Caitilin Andrews-Lee (2021). (1st September 2021) - Gindin, Irene
Review of: The Emergence and Revival of Charismatic Movements: Argentine Peronism and Venezuelan Chavismo, Caitilin Andrews-Lee (2021)Cambridge: Cambridge University Press, 251 pp., ISBN 978-1-10883-147-5, h/bk, £75.00